First principle DFT+U study on the structural, dynamical, and electronic properties of multiferroic BiFe0₃ / Muhamad Zafrol Jusoh - Jusoh, Muhamad Zafrol (2013)
The structural and electronic properties of BiFe0₃ (BFO) were investigated employing the first principles within LSDA.+U method. In this work the orthorhombic perovskite structure is used. The value correlation U is varied at OeV, 3eV and 6eV which found that 6eV calculated band gap is more closed to the experimental one. For geometry optimization the volume is found to be underestimation when it is compared to experimental data. The band gap of BFO was found to be 2.0eV by the electronic structure calculation. Analysis of the density of states indicated that the valence band was consisted with Fe-d and O-p states, and the conduction band was composed of Fe-d and Bi-p states.